The spectrum of Vogt-Koyanagi-Harada disease in Turkey: VKH in Turkey - (:unkn) unknown (My University, 2007)
Aim: The aim of this report was to provide a detailed description of the clinical features of Vogt-Koyanagi-Harada (VKH) disease in Turkish patients. Methods: We retrospectively analyzed 45 patients diagnosed with VKH disease at seven referral centers in Turkey. A standard data acquisition form was used for the analysis of demographic and clinical features. Results: The study cohort consisted of 45 patients (32 female, 13 male) who had a mean age at presentation of 31 years. Seven patients (15%) were aged 16 years or younger. Nineteen (42%) patients presented in the acute or subacute stage and 26 (58%) in the chronic stage. According to the revised diagnostic criteria, nine (20%) patients had the complete form of the disease, 23 (51%) had the incomplete form, and 13 (29%) had probable VKH disease. All patients had bilateral ocular involvement. Sunset-glow fundus was observed in 89% of the patients, pigment clumping in 73%, nummular depigmented scars in 71%, cataract in 53%, optic atrophy in 31%, glaucoma in 29%, subretinal fibrosis in 22%, choroidal neovascular membranes in 7%, and phthisis in 4%. All patients who presented at the acute uveitic stage received systemic corticosteroid therapy. Immunosuppressive treatment was employed in 30 (66%) patients, which was initiated at the acute uveitic stage in ten (22%) patients. Final visual acuity was better than 0.5 in 59% of the patients' eyes, between 0.1 and 0.5 in 21%, and less than 0.1 in 20%. Conclusions: VKH disease is rare in Turkey. We conclude that the majority of patients with VKH in Turkey do not have the complete form of the disease. Based on our results, most patients with VKH seem to be late referrals. Ocular complications were common among these patients. © Springer Science+Business Media B.V. 2006.
Keywords: Ocular complication; Visual acuity; Vogt-Koyanagi-Harada disease